Environmental education and perception of the population on the excessive use of plastic bags in the city of Juliaca – Peru - J.C., QUISPE MAMANI; S.L., AGUILAR PINTO; D.E., BARRA QUISPE; A., MAMANI FLORES; T.L., BARRA QUISPE; C.R., YAPUCHURA SAICO; H.R., HUILLCA MALDONADO (The journal of contemporary issues in business and government, 2021)
The objective of this research was to establish the perception of the population about the excessive use of plastic bags in the city of Juliaca, in addition to determining the relationship between the socioeconomic level and the level of perception about the excessive use of plastic bags and determine if environmental education within the city of Juliaca will contribute to reducing the use of plastic bags. A non-experimental, quantitative methodology was applied with a multinomial Logit model, where the primary data were collected from questionnaires that were carried out on a sample of 380 consumers and were processed in the SPSS statistic. The model has shown that 67.37% of the population of Juliaca shows concern and is aware of the problem caused by the excessive use of plastic bags and 80.26% are informed about the negative effect it causes on the environment, but they have no knowledge about which one, it is the friendliest packaging. Finally, the environmental education of the residents contributes to the reduction of plastic bags, since the relationship between the reduction in the use of plastics, with the knowledge about the existence of ecological bags, reuse of plastic bags and environmental awareness is direct; while replacing plastic with another material inversely affects the low reduction in the use of plastic bags.